2018
DOI: 10.1007/s00213-018-4869-9
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of avermectins as novel therapeutic agents for alcohol use disorders

Abstract: The deleterious effects of alcohol use disorders (AUDs) on human health have been documented worldwide. The enormous socioeconomic burden coupled with lack of efficacious pharmacotherapies underlies the need for improved treatment strategies. At present, there is a growing body of preclinical evidence that demonstrates the potential of avermectins [ivermectin (IVM), selamectin (SEL), abamectin (ABM), and moxidectin (MOX)] in treatment of AUDs. Avermectins are derived by fermentation of soil micro-organism, Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 126 publications
0
9
0
2
Order By: Relevance
“…Four different types of AVM were tested for their potential as anti-alcohol therapy, namely selamectin (SEL), abamectin (ABM), ivermectin (IVM) and moxidectin (MOX). IVM modulates the action of ethanol on P2X4Rs in an in vivo study, which may be associated with a decrease in alcohol intake [124]. Also in both male and female mice of the C57BL/6J strain.…”
Section: Anti-alcohol Therapiesmentioning
confidence: 95%
“…Four different types of AVM were tested for their potential as anti-alcohol therapy, namely selamectin (SEL), abamectin (ABM), ivermectin (IVM) and moxidectin (MOX). IVM modulates the action of ethanol on P2X4Rs in an in vivo study, which may be associated with a decrease in alcohol intake [124]. Also in both male and female mice of the C57BL/6J strain.…”
Section: Anti-alcohol Therapiesmentioning
confidence: 95%
“…The triple combination of cepharanthine (an anti-inflammatory alkaloid from Stephania cepharantha Hayata), (CAS number: 48,104,902), selamectin (an avermectin isolated from Streptomyces avermitilis and used as an anti-helminthic and parasiticide drug in veterinary medicine), (CAS number. 220119−17-5), and mefloquine hydrochloride (Lariam™, used for the prophylaxis and treatment of malaria) [57][58][59] has recently been shown to inhibit infection of simian Vero E6 cells with pangolin coronavirus GX_P2V/2017/Guangxi (GX_P2V), whose S protein shares 92.2 % amino acid identity with that of SARS-CoV-2 [60]. Further, it was demonstrated that GX_P2V also uses ACE2 as the receptor for viral cell entry [60].…”
Section: Cepharanthine/selamectin/mefloquine Hydrochloridementioning
confidence: 99%
“…Rather than deleterious, the P2X4R expression and function in the brain reward system have been associated with salutary effects in alcohol abuse. Ethanol is a preferential inhibitor of the P2X4R, a situation that can be overcome by positive allosteric modulators, like ivermectin or derivates, which have been shown to reduce ethanol drinking behavior (reviewed in [200,201]).…”
Section: Is There a Dark Side Of P2x4 Receptor Activation Outside Thementioning
confidence: 99%